2019
DOI: 10.1021/acs.jpcc.9b04174
|View full text |Cite
|
Sign up to set email alerts
|

Gaining Insight into the Underlayer Treatment for in Situ Fabrication of Efficient Perovskite Nanocrystal-Based Light-Emitting Diodes

Abstract: The feasibility of in situ fabrication of metal halide perovskite films for optoelectronic devices has attracted increasing research interest as it eliminates the material preparation step and thus simplifies the integration procedure. The success of in situ fabrication requires delicate regulations of the underlayers. Poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) is a universal hole transporting material for solution-processed optoelectronic devices; however, it is usually hard to cast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…In 2019, Zhong's group improved the HTL of PeLED and used oxygen plasma-treated PEDOT:PSS. [83] The surface of PEDOT:PSS was enriched with PSS after oxygen plasma treatment, and the material thickness was reduced, which promoted the crystallization and uniform growth of FAPbBr 3 nanocrystals on the surface and reduced cracks and pinholes. After 10 minutes of oxygen plasma treatment, the PLQY of the perovskite film increased from 42 % to 58.7 %, and the maximum brightness increased from 6865 cd/m 2 (4.3 V) to 19790 cd/m 2 (4.4 V).…”
Section: Light Emitting Diodementioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, Zhong's group improved the HTL of PeLED and used oxygen plasma-treated PEDOT:PSS. [83] The surface of PEDOT:PSS was enriched with PSS after oxygen plasma treatment, and the material thickness was reduced, which promoted the crystallization and uniform growth of FAPbBr 3 nanocrystals on the surface and reduced cracks and pinholes. After 10 minutes of oxygen plasma treatment, the PLQY of the perovskite film increased from 42 % to 58.7 %, and the maximum brightness increased from 6865 cd/m 2 (4.3 V) to 19790 cd/m 2 (4.4 V).…”
Section: Light Emitting Diodementioning
confidence: 99%
“…Applied to PeLED, the luminous efficiency reached 403 cd/m 2 , the EQE reached 2.8 %, and as the voltage increases, it exhibited a stable emission peak. In 2019, Zhong's group improved the HTL of PeLED and used oxygen plasma‐treated PEDOT:PSS [83] . The surface of PEDOT:PSS was enriched with PSS after oxygen plasma treatment, and the material thickness was reduced, which promoted the crystallization and uniform growth of FAPbBr 3 nanocrystals on the surface and reduced cracks and pinholes.…”
Section: Application Of Organic‐inorganic Hybrid Perovskite Nanomatermentioning
confidence: 99%
“…It has been reported that the substrate not only affects the carrier transport and recombination process during device operation , but also have a significant influence on the crystallization kinetics of perovskite films . Chang’s group used oxygen-plasma treatment to tune the morphology and surface molecular composition of the poly­(3,4-ethylenedioxythiophene):poly­(styrenesulfonate) (PEDOT:PSS) substrate that enabled them to achieve a 4-fold enhancement of current efficiency (CE) in green PeLEDs . Zhang and colleagues observed the existence of N–H hydrogen bonding between polymeric hole-transport materials as the substrates and the organic cation spacer, and suggested that such an interaction can significantly refine the grain size of quasi-2D perovskites .…”
Section: Introductionmentioning
confidence: 99%
“…We invoke a simple and facile method, oxygen-plasma treatment on the PEDOT:PSS film, 30 to modulate the HIL/ HTL interface. PEDOT:PSS films were treated by oxygen plasma for 4 min (see Supporting Information for details).…”
mentioning
confidence: 99%